Application of Codes Performance‐Based Design Procedures for a Tall Building Using Recorded and Spectrally Modified Ground Motions. (25th June 2020) - Rezaei, Rahim; Tariverdilo, Saeed; Sheidaii, Mohammad Reza; Khodabandehlou, Ashkan
Summary: There is a growing tendency toward the performance‐based design of tall buildings, where any assessment using response history analysis requires a set of ground motion (GM) records. This paper considering a tall building as a case study investigates how judgment on the seismic safety of the structure is affected by the use of recorded or spectrally matched GMs. Three model structures are developed: (a) using conventional design procedure of Chapter 12 of ASCE 7‐16; (b) adopting linear analysis requirements of Chapter 16 of ASCE 7‐16; (c) designing for service‐level design earthquake of Los Angles Tall Building Structural Design Council (LATBSDC) procedure. It is shown that all of the structures give acceptable performance when subjected to simulated GMs, although this is not the case for amplitude‐scaled GMs based on ASCE 7‐16 and LATBSDC. Finally, to have an objective assessment of performance, independent of GM types, incremental dynamic analysis is employed to derive fragility and mean annual rate of exceeding (MAR). Results show that for anticipated drifts at Maximum Considered Earthquake (MCE) level, the structures provide acceptable MAR at the fundamental period. However, for the higher modes including the second and third periods, MAR values become acceptable only at drifts as large as 0.085.